Comparison of platelet-rich plasma versus corticosteroid injection for adhesive capsulitis: a randomised controlled trial - Karak, Anshuman; Naik, Ashish (International Journal of Research in Orthopaedics, 2025)
Background: Adhesive capsulitis is characterized by pain and progressive restriction of shoulder range of motion. Corticosteroid injections are routinely used for short‑term pain relief, whereas platelet‑rich plasma (PRP) contains bioactive growth factors that may promote longer‑lasting recovery. Evidence comparing these treatments is conflicting and optimal therapy is still unclear. Objectives of the study were to compare the efficacy and safety of a single ultrasound‑guided intra‑articular PRP injection versus a corticosteroid injection for pain relief, functional recovery and range of motion (ROM) in adults with primary adhesive capsulitis. Methods: In this prospective randomised trial, 40 adults (mean age 54 years) with idiopathic adhesive capsulitis were randomly allocated to receive either a 4 ml autologous PRP injection or 40 mg of triamcinolone acetonide under ultrasound guidance. A computer‑generated random sequence and sealed opaque envelopes ensured allocation concealment; patients and outcome assessors were blinded. Baseline evaluations included visual analogue scale (VAS) pain scores, Constant–Murley score (CMS), shoulder pain and disability index (SPADI), and passive ROM in forward flexion, abduction, external and internal rotation measured by goniometer. Follow‑ups were performed at 6 weeks, 3 months and 6 months. The primary outcome was change in VAS at 6 months; secondary outcomes included CMS, SPADI, ROM, patient satisfaction (Likert scale) and adverse events. Data were analysed with independent t‑tests and χ² tests using statistical package for the social sciences (SPSS) v26 with p<0.05 considered statistically significant. Results: Baseline characteristics were comparable between groups. At 6 months, patients in the PRP group demonstrated greater reductions in VAS scores (1.7±0.7 versus 3.1±0.9; p<0.001), higher CMS (80±5 versus 65±6; p<0.001) and lower SPADI scores (20±6 versus 35±7; p<0.001) compared with the corticosteroid group. Gains in forward flexion (150±10° versus 130±12°; p<0.001), abduction (140±9° versus 120±10°; p<0.001), external rotation (60±5° versus 50±6°; p<0.001) and internal rotation (70±6° versus 55±7°; p<0.001) were also significantly larger with PRP. Clinically meaningful pain reduction was observed in 88% of PRP recipients compared with 48% of those receiving corticosteroid injections. Functional improvement and ROM gains occurred in 82% and 80% of PRP patients but in only 48% and 2% of corticosteroid recipients, respectively. High satisfaction (Likert ≥4) was reported by 70% of PRP‑treated patients versus 40 % in the steroid group. No serious adverse events occurred. Conclusions: A single intra‑articular PRP injection provided superior and sustained improvements in pain, shoulder function and ROM compared with corticosteroid injection at 6 months, with a higher proportion of satisfied patients and no significant safety concerns. PRP may therefore be considered an effective longer‑term option for managing adhesive capsulitis - whereas corticosteroids provide only short‑term relief.